EFFECT OF POLY (N- VINYPYRROLIDONE) ON THE NON-ISOTHERMAL CRYSTALLIZATION KINETICS AND VISCOELASTIC PROPERTIES OF PVDF FILMS - Mashak,A. (2016)
Abstract Poly(vinylidene fluoride) (PVDF) and PVDF blends with various molecular weights of poly (N- vinylpyrrolidone) (PVP) films were prepared in dimethyl formamide through the solution casting method. Non-isothermal melt crystallization studies of PVDF films were carried out by cooling the molten samples at different temperatures using differential scanning calorimetry (DSC). The obtained films have been characterized by dynamic mechanical thermal analysis (DMTA). Crystallization kinetics of PVDF films were successfully described by the Jeziorney, Mo and Ziabicki models. The Ozawa equation was found to be invalid for describing the crystallization kinetics. Kinetic parameters such as t1/2, Zc and F(T) indicated that the crystallization rate decreased for PVDF/PVP films as compared to neat PVDF films and was affected by the molecular weight of PVP. The results based on Ziabicki's model revealed that the addition of PVP decreased the ability of PVDF to crystallize under non-isothermal melt crystallization conditions. The activation energy was calculated through Friedman and advanced isoconversional methods. Results showed that the addition of PVP to PVDF films caused an increase in activation energy. By comparing DMTA results of PVDF/PVP blends with neat PVDF films, it could be concluded that blending PVDF with PVP caused an increase in the glass transition temperature (Tg) while the storage modulus was decreased.